Chlorpyrifos and Cypermethrin Induce Apoptosis in Human Neuroblastoma Cell Line SH‐SY5Y. (25th July 2014) - Raszewski, Grzegorz; Lemieszek, Marta Kinga; Łukawski, Krzysztof; Juszczak, Małgorzata; Rzeski, Wojciech
Abstract Our previous in vivo studies showed that chlorpyrifos (CPF) and cypermethrin (CM) in a mixture dermally administered, strongly inhibited cholinesterase activity in plasma and the brain and were very toxic to the rat central nervous system. In this work, the mechanisms of neurotoxicity have not been elucidated. We used human undifferentiated SH‐SY5Y cells to study mechanisms of pesticide‐induced neuronal cell death. It was found that chlorpyrifos (CPF) and its mixture with cypermethrin (CPF+CM) induced cell death of SH‐SY5Y cells in a dose‐ and time‐dependent manner, as shown by MTT assays. Pesticide‐induced SH‐SY5Y cell death was characterized by concentration‐dependent down‐regulation of Bcl‐2 and Bcl‐xL as well as an increase in the caspase 3 activation. Pan‐caspase inhibitor Q‐VD‐OPh produced a slight but significant reversal effect of pesticide‐induced toxicity indicating that the major caspase pathways are not integral to CPF‐ and CPF+CM‐induced cell death. Furthermore, signal transduction inhibitors PD98059, SL‐327, SB202190, SP600125 and mecamylamine failed to attenuate pesticides effect. Atropine exhibited minimal ability to reverse toxicity. Finally, it was shown that inhibition of TNF‐α by pomalidomide attenuated CPF‐/CPF+CM‐induced apoptosis. Overall, our data suggest that FAS/TNF signalling pathways may participate in CPF and CPF+CM toxicity.